ATH-03 Eus tissue sampling with fork-tip biopsy needle in the diagnosis of type 1 autoimmune pancreatitis. (June 2019) - Oppong, Kofi; Maheshwari, Pardeep; Haugk, Beate; Leeds, John; Huggettt, Matthew; Paranandi, Bharat; Darne, Antony; Nayar, Manu
Abstract : Introduction: Endoscopic ultrasound (EUS) fine needle aspiration (FNA) has poor performance in diagnosing autoimmune pancreatitis (AIP) due to small sample size and lack of preserved tissue architecture. In mass forming disease non-diagnostic EUS-FNA may result in a presumptive diagnosis of malignancy and unnecessary surgery. A core biopsy needle with a novel fork-tip design (SharkCore™) has been introduced with the aim of improving yield and maintaining tissue architecture. Literature on its performance in the diagnosis of AIP is limited to a few case reports. Aim: To assess the diagnostic performance of EUS tissue sampling with a fork-tip needle in the diagnosis of type 1 AIP. Methods: Retrospective review of a prospectively maintained AIP database in a tertiary center to identify patients with a final diagnosis of type 1 AIP who underwent EUS-TS during diagnostic workup. Pathology reports were reviewed and classified as per International Consensus Diagnostic Criteria (ICDC); Level 1 (highly suggestive) requires the presence of 3 or all 4 histological features and level 2 (probable) requires 2 features. Results: Between March 2006 and November 2018, 35 procedures were performed on 28 individuals (29 lesions) with a final diagnosis of Type 1 AIP. Mean age ( ± SD) 63 (±11.4), 21 male. 29 procedures were for a mass lesion and or biliary obstruction. 2 patients underwent surgical resection and 2 laparoscopic biopsy. There were 8 procedures with an FNA needle, 7 reverse bevel and 20 fork-tip. There were 6 inadequate samples (3 FNA, 2 reverse bevel and 1 fork-tip). Of the 29 adequate samples, 15 (51.7%) met ICDC criteria for diagnosis of AIP all at level 1. 0/13 FNA or reverse bevel samples were diagnostic compared to 15/19 (79%) fork-tip samples (p=0.0001). Obliterative phlebitis was identified in 10/19 (52.6%), storiform fibrosis in 14/19 (70%), dense lymphoplasmocytic infiltrate in 14/19 (70%) and IgG4 positive plasma cell count > 10 per high power field in 14/19 (70%) of adequate fork-tip samples. Of the 17 individuals who underwent 20 procedures (2 repeat and 1 sampling of 2 separate lesions) with a fork-tip needle, 14 (83.2%) had a final ICDC level 1 diagnostic fork-tip biopsy. Conclusion: In this the largest study to date of the fork-tip core biopsy needle in the diagnosis of AIP, the needle demonstrated very good overall diagnostic performance. This study supports the preferential use of this needle in suspected type 1 AIP.